ReMap 2020: a database of regulatory regions from an integrative analysis of Human and Arabidopsis DNA-binding sequencing experiments. Issue Volume 48:Issue D1(2020) (29th October 2019) - Chèneby, Jeanne; Ménétrier, Zacharie; Mestdagh, Martin; Rosnet, Thomas; Douida, Allyssa; Rhalloussi, Wassim; Bergon, Aurélie; Lopez, Fabrice; Ballester, Benoit
Abstract: ReMap (http://remap.univ-amu.fr ) aims to provide the largest catalogs of high-quality regulatory regions resulting from a large-scale integrative analysis of hundreds of transcription factors and regulators from DNA-binding experiments in Human and Arabidopsis ( Arabidopsis thaliana) . In this 2020 update of ReMap we have collected, analyzed and retained after quality control 2764 new human ChIP-seq and 208 ChIP-exo datasets available from public sources. The updated human atlas totalize 5798 datasets covering a total of 1135 transcriptional regulators (TRs) with a catalog of 165 million (M) peaks. This ReMap update comes with two unique Arabidopsis regulatory catalogs. First, a catalog of 372 Arabidopsis TRs across 2.6M peaks as a result of the integration of 509 ChIP-seq and DAP-seq datasets. Second, a catalog of 33 histone modifications and variants across 4.5M peaks from the integration of 286 ChIP-seq datasets. All catalogs are made available through track hubs at Ensembl and UCSC Genome Browsers. Additionally, this update comes with a new web framework providing an interactive user-interface, including improved search features. Finally, full programmatically access to the underlying data is available using a RESTful API together with a new R Shiny interface for a TRs binding enrichment analysis tool.